PENGARUH DAN EFISIENSI PENGGUNAAN INPUT PADA USAHATANI LADA PUTIH (MUNTOK WHITE PEPPER) DI DESA TERENTANG III KECAMATAN KOBA KABUPATEN BANGKA TENGAH - Iwan Setiawan, Angga Satria, Yudi Sapta Pranoto dan (Jurnal Buana Agribisnis, 2014)
ABSTRACTThe purpose of this research is: (1) to calculate the amount of imcome from white pepper plantation in Terentang III Village (2) to analyze what input that has real effect on the production of white pepper production in Terentang III Village, (3) to analyze the level of efficiency of input use in white pepper farming in Terentang III Village. The research shows that (1) the profit made from the white pepper farming in Terentang III Village in the first harvest is Rp 31 479 285, (2) the input of fertilizer (X1) andthe input of herbicide (X3) have significant effect on the production of white pepper on the level of trust of 95 percent, while the input of labors (X2) does not have significant effect on the production of white pepper on the level of trust of 95 percent, (3) the use of fertilizer input (X1), labor (X2), and herbicide (X3) in the white pepper farming in Terentang III Village is not yet efficient, hence the need of addition.Keywords: effect, efficiency, input, farming, white pepper